Message And File Transfering Using Key Exchange Protocol Over Secure Network Communication - Vijayan, Reshmi; Sreedivya RS, Sreedivya RS (International Journal of Computer Sciences and Engineering, 2018)
Authenticated Key Exchange (AKE) protocol allows to communicated each other using a generate session key for suitable and secure communication. The server side will generate a session key after giving approval by the client profile. Clients can view other clients of same group who is online at the time. During the message or file transfer both encryption and decryption takes place automatically using RSA algorithm with a symmetric key. Finally the administrator can also monitoring what all take place in the client side by using remote sensing capability. File transfer take place between the user and client with more security. For the communication purpose here it is using intranet so that it can be easily find out the IP address of the server and client. The proposed system will be give more important to the file transferring, remote sensing. The other speciality of the proposed system is key freshness that takes place periodically. The proposed system will be more secure for file transferring over the network communication.